Odzyskanie poczucia umiaru - Francisa Fukuyamy obrona klasycznego liberalizmu (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The article points mainly to the threat which, according to Fukuyama, is posed by taking fundamental ideas of liberalism to extremes. It shows the consequences of such “radicalism”, but also personal remedies, a specific defense that Fukuyama proposes against such “radicalizations”. In the beginning, the author illustrates how Fukuyama views classical liberalism. He then presents examples of liberal “radicalism” which pose a particular threat towards liberal practice and thought. Liberal ideas taken to extremes undermine the basic principles of liberalism, which can be easily noticed in the case of neoliberalism and the politics of individuality. At the end, the author elaborates on an idea only briefly mentioned by Fukuyama, but so important in the context of those acknowledged threats, the ideas of prudence, moderation, and a certain type of restraint. Fukuyama is certain that abandonment is not the answer to the current stir over liberalism, but its moderation, as he states at the end of his book “regaining moderation”, as individuals and members of society.